LABOUR PRODUCTIVITY: MYTHS AND REALITIES - Kapelyuk, Zoya (Revista Inclusiones, 2020)
Labour productivity in the study is considered to be one of the broadest measure, characterizing national economic situation, and also as the indicator of performance. The relevance of the study implies that this issue has not yet received sufficient light. The labour productivity in the Russian Federation is significantly lower than in the United States and European countries. The switch to a market economy marked the unreasonable absence of this rate, it was entirely off the official statistics, and enterprises significantly reduced the service of labour management. In this regard, this article aims to identify the main factors for the growth of labour productivity. The leading approach to the study of this issue is an integrated approach to transforming the organizational culture of the enterprise and its collective thinking. The article presents the means for increasing labour productivity and successful business development, such as workforce and talent management, the inducement system of employment management. The content of the article is of great practical assistance to the chief executive officers, willing to address the problems of labour productivity improvement in a comprehensive way